The Academy of Fine Arts Graduate (1925) Architect: Huseyin Husnu Tumer - Degirmenci, Ali; Pilehvarian, Nuran Kara (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2021)
The present study aims to investigate educational processes, architectural projects, professional activities and design methodology of the revered Architect Huseyin Husnu Tumer. Tumer was born in Istanbul in 1900 and graduated from Sanayi-i Nefise-i Sahane Mektebi (Academy of Fine Arts) in 1925. In this research, Huseyin Husnu Tumer's professional career is analyzed in five phases. The first phase begins with his education and covers the time period between his graduation and returning from Jerusalem in 1927. In the academy, Tumer completed his education as a student of another well-known and respected architect, Giulio Mongeri. After his graduation, as a young architect, Tumer was commissioned in a team headed by Mimar Kemalettin, which included architect Mehmet Nihat Nigizberk, Engineer Rustu, Cemal and Mimar Kemalettin's son, architect Sinan Mimaroglu, with the task of restoration of Al-Aqsa Mosque in Jerusalem. The second phase includes the short time period after the Jerusalem years and a general outlook of Republican architecture. After returning to Turkey around 1927, he continued to work as a project architect for a while and participated in several architectural competitions. During this period, he worked as a project manager in Bursa Spa Hotel Project which designed by his mentor, Giulio Mongeriand he designed some parts of the Project all by himself. Also, he achieved the first place awards in two project competitions, these being Bursa Municipality Tuz Pazari Market Hall Building competition and Ankara Sanayi and Maadin Bank project competitions. The third phase includes production of several apartment buildings and his professional activities at the beginning of 1930's. In this period, Tumer completed apartments such as Istanbul Ayazpasa Engineer Ibrahim Galip B. Apartment, Istanbul Munip B. House and Istanbul Nisantasi Husnu B. Apartment, and Istanbul Taksim Talimhane Istiklal Apartment with Torkum Cubukciyan. Also in 1933, he designed a gas station in Eminonu for an American Oil Company Socony Vacuum. Following this period, in 1934, Tumer, participated in few architectural competitions. He achieved the first prize in Ankara Child Protection Agency Apartment (Cocuk Esirgeme Kurumu Himaye-i Etfal Apartmani) project competition, the second prize in Yalova Thermal Hotel project competition, the third prize in Ministry of Customs and Exclusivity (Gumruk ve Inhisarlar Vekaleti) building project competition and the fourth prize in Ankara Sumerbank Office Building project competition. As a result of the competition, Ankara Child Protection Agency Apartment was built in 1935 in Ankara Yenisehir. The fourth phase includes his works for public institutions in Ankara. In 1937, he was appointed as an architect of Ankara Province Municipality (Ankara Vilayeti Belediyesi). After 5 years, in 1942, Tumer was appointed to the Ministry of Public Works, office of Construction and Planning Works (Nafia Nezareti Yapi ve Imar Isleri Reisligi) in Ankara. In 1942, he also achieved the first prize in Ankara Haymana Thermal Hotel project competition together with architect Torkum Cubukciyan. In 1946, he was appointed to the office of the ministerial counsellor in Ministry of Public Works. In 1946 and 1947 he acted as a jury member in project competitions such as Ankara Technical University Pyhsic and Chemistry Faculty building and Istanbul University Law and Economy Faculty building, on behalf of Ministry of Public Works. The fifth and last phase includes Tumer's professional activities in Istanbul. Around 1948, Tumer's time working for the, Ministry of Public Works was over and he was appointed as a project manager in Istanbul University project and moved from Ankara to Istanbul. In 1953, he was appointed as the Istanbul Municipality deputy mayor and worked until 1955. In 1955, he was sent to Jerusalem to review the tiles adorning the Omer's Mosque. After retirement, Tumer died in 1968. Although his work with effective architects, such as Giulio Mongeri, and Architect Kemaleddin, Husnu Tumer can be regarded as an active but not a well-known name in the current literature of Turkish architecture. It can be said that his education with Giulio Mongeri shaped his modernist/cubist architectural identity. Therefore, the earliest apartment buildings he designed at the beginnings of 1930's are examples of early phase modern thoughts, bearing the design criteria of cubist architecture. In order to define Tumer's professional activities, correspondences in the Republic Archive, photos in Salt Research Architecture and Design Archive and articles published in Mimar/Arkitekt magazine were examined within the scope of the research. As a result of this study, Huseyin Husnu Tumer's completed projects, employments, competitions in which he won prizes, jury participations and articles about his projects were determined and professional activities of an insufficianly known and effective architect and his contributions to architecture of the Republic of Turkey were revealed.
Keywords: Bursa Thermal Hotel; Engineer Ibrahim Galip B. Apartment; Huseyin Husnu Tumer; The Academy of Fine Arts; Turkish Republican Architecture; Architecture